Preventive effects of consuming nutritional supplement of Morinda Citrifilia L. on bax and bcl-2 in early leukemic rats - Haron, Nursyuhada (2012)
The most common cancer in Malaysia includes leukaemia and lymphoma. Cancer has been linked with the failure of apoptosis process regulated by Bcl-2 family genes, consisting of pro apoptotic genes such as Bax and anti apoptotic genes such as Bcl-2. The ratio of Bcl-2:Bax determines susceptibility towards apoptosis. Meanwhile, Morinda citrifolia fruit is known to exhibit anticancer properties. Thus, the objectives of this study were to determine the anticarcinogenic and preventive effects of M. citrifolia fruit in rats with early leukaemia/lymphoma induced by N-Methyl-N-Nitrosourea (MNU). Male Sprague Dawley rats were divided into four groups; Group 1 (control group), Group 2 (M. citrifolia fruit treated group), Group 3 (MNU treated group) and Group 4 (leukaemia/lymphoma prevention group treated with M. citrifolia fruit). The rats in the Group 3 and Group 4 were injected with four intraperitoneal injections of the MNU mixture, at a dose of 60 mg/kg of body weight per injection, twice a week for two consecutive weeks with a total dose of 240 mg/kg of body weight. Rats in Group 1 and Group 2 were injected with normal saline following the same procedure. Ground dried M. citrifolia fruit at the dose of 3000 mg/kg of body weight were supplemented daily to the rats in Groups 2 and 4 for 12 weeks. Blood samples were taken at week 0, week 4 and week 8 of experimental study via cardiac puncture. At week 12, all rats were sacrificed and blood samples were taken via posterior vena cava. RNA were extracted from the blood and the relative transcription of Bcl-2 and Bax were quantified using Eva Green quantitative real time reverse transcription-PCR. For haemogram and serum biochemical analyses, blood samples were taken at week 4, week 8 and week 12 of the experimental study and analysed using automated blood analysers. For histopathological examination, organs were taken after sacrifice at the end of the experimental period. The organs were spleen, lymph nodes, liver, kidneys, lung and heart. The organs were processed using standard methods and stained with hematoxylin and eosin (H&E). Quantitative real time RT-PCR assays (qRT-PCR) for quantification of Bax and Bcl-2 genes which were successfully developed using an Eva Green dye showed that the ratio of Bcl-2:Bax in the rats injected with MNU was significantly higher compared to other groups. Significant reduction of Bcl-2:Bax ratio in Group 4 at week 12 showed that M. citrifolia fruit limits the progression of leukaemia/lymphoma through regulation of apoptosis gene transcription. Intraperitoneal injections of MNU at a total dose of 240 mg/kg of body weight successfully induced leukaemia without lymphocytosis in Group 3 at 50% and 75% after 8 weeks and 12 weeks of injection, respectively. Meanwhile, supplementation of dried M. citrifolia fruit did not significantly reduce the percentages of leukaemia without lymphocytosis in Group 4 at 20% and 60% after 8 weeks and 12 weeks of injection, respectively. All blood results obtained from the automated analysers in rats injected with MNU were similar to the control. All organs were macroscopically normal. Histopathology results showed that the rats in Group 3 developed 100%, 50% and 25% early lymphoma lesions in the spleen, mesentric lymph nodes and other lymph nodes respectively. Meanwhile, histopathology results showed that the rats in Group 4 developed 100%, 80% and 20% early lymphoma lesions in the spleen, mesentric lymph nodes and other lymph nodes respectively. Lesion scoring results showed that supplementation of M. citrifolia fruit at the dose of 3000 mg/kg of body weight did not significantly reduced the incidence of leukaemia and lymphoma Group 4.